Study on the Influence of Excitation in Sliding Construction of Long Span Steel Structure. Issue 3 (April 2021) - Zhou, Qinghui; Zhang, Chenlong; Xiao, Long; Zhang, Xiwang; Xie, Yidong
Abstract: There is a safety risk on sliding construction because of the unstable state of large-span steel structure. The core technology of sliding construction is synchronous control. In this paper, a large-span steel structure sliding construction is taken as an example. The span reaches 202.2 m, which is the first case in China. Based on the theoretical analysis of the sliding process, the mathematical sliding model is established, and the main parameters are analyzed. The displacement and synchronization error under the external exciting force are calculated. The sliding motion, mechanical properties are studied. It also provides measures to improve synchronization performance. The result has proved that the scheme effectively guarantees the construction safety and quality. So it is also a reference for the design and development of the synchronous control.